THE ROLE OF META-SUBJECT COMPETENCE IN THE DEVELOPMENT OF STUDENTS’ LANGUAGE SKILLS AND STRATEGIES FOR ITS ENHANCEMENT (KONFERENSIYA, 2025)
The article explains what meta-subject competence is and why it isimportant in education. It shows that these universal skills—such as thinking,problem-solving, communication, and self-control—help students learn better in allsubjects and connect knowledge between them. The article also describes howteachers can develop these skills through joint projects, reflection, and teamwork,helping students form a broader understanding of the world and prepare for real-lifesituations